Pengaruh Financial Self Efficacy, Perilaku Keuangan, Keterampilan Wirausaha dan Financial Technology Terhadap Kinerja Keuangan UMKM - Rochmawati, Putri; Mawardi, M. Cholid; Sari, Arista Fauzi Kartika (Universitas Islam Malang, 2024)
This research aims to determine the influence of financial self efficacy, financial behavior, entrepreneurial skills and financial technology on the financial performance of MSMEs. Through a quantitative approach, data will be collected from MSMEs in Malang City. The results of this research are: 1) financial self efficacy has a significant effect on the financial performance of MSMEs, 2) financial behavior has a significant effect on the financial performance of MSMEs, 3) entrepreneurial skills have a significant effect on the financial performance of MSMEs, 4) financial technology has a significant effect on financial performance MSMEsKeywords: MSME financial performance, financial self efficacy, financial behavior, entrepreneurial skills and financial technology